KARDIOCHIRURGIA DOROSŁYCHImpact of selected factors on changes of perioperative blood lactate concentration, in patients undergoing on-pump coronary bypass surgery - Wilczyński, Mirosław; Krzych, Łukasz; Gierek, Danuta; Białek, Krzysztof; Bochenek, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduce: Blood lactate concentration reflects the proportion between tissue oxygen supply and demand. Therefore, the blood lactate level of cardiac surgical patients may have an important prediction value. Aim: The authors of the study have tried to assess the impact of selected perioperative factors on blood lactate concentration in patients undergoing on-pump coronary bypass surgery. Material and Methods: We reviewed data from 132 patients who underwent CABG with cardiopulmonary bypass (CPB). Basic demographic and clinical data such as age, sex, BMI, NYHA class, CCS class, diabetes, hypertension, haemoglobin and haematocrit level, also EUROSCORE and logistic EUROSCORE have been analyzed. Furthermore, cardiopulmonary bypass time (CPBT), cross-clamp time (CCT) and postoperative haematocrit and haemoglobin level were analyzed. Arterial blood lactate concentration was measured four times: twice before the operation – prior and post anaesthetic induction – and twice after surgery – around 12 and 24 hours postoperatively. Results: The analysis of several factors showed that postoperative blood lactate concentration depends on CPBT (positive correlation), postoperative haemoglobin level (negative correlation) and preoperative lactate concentration (negative correlation) and the correlation for these factors is statistically significant. Furthermore, perioperative and postoperative lactate concentration had a statistically significant correlation with EUROSCORE level and logistic EUROSCORE. Conclusion: The above data confirm the usefulness of measuring blood lactate concentration as an important diagnostic factor for postoperative complications.